2021
DOI: 10.1007/978-3-030-85969-5_69
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Learning Scheme to Up-skilling and Re-skilling – Designing a Collaborative Training Program Between Industry and Academia Towards Digital Transformation

Abstract: Small and medium-sized enterprises (SMEs) in Europe are conscious that their competitive position depends on their success to embrace digitalisation challenges. However, some decision-makers in companies discard digital transformation because they do not understand how it can be incorporated into their businesses. Therefore, academia, research centres, and technological clusters are responsible for building the infrastructures and providing the support and the training that will progressively change this minds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
0
0
Order By: Relevance
“…Furthermore, (Simões, et al, 2021) found a positive correlation between industry and academia, and reskilling and upskilling are gaining ground in the literature. Reskilling, according to them, entails acquisition of skills sets that result in getting new career opportunities.…”
Section: Literature Reviewmentioning
confidence: 96%
See 2 more Smart Citations
“…Furthermore, (Simões, et al, 2021) found a positive correlation between industry and academia, and reskilling and upskilling are gaining ground in the literature. Reskilling, according to them, entails acquisition of skills sets that result in getting new career opportunities.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Upskilling, the process of expanding an employee's skill set (generally by adding to an existing body of knowledge), offers a much-needed solution to this challenge. Unlike upskilling, which focuses on adding to an existing skill set within a role (for instance, due to new technology), reskilling refers to the process of learning new skills needed to do an entirely different job (Simões, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation